2000
DOI: 10.1002/1097-4628(20001213)78:12<2081::aid-app40>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of trithiocyanuric acid with oxiranes. II. Kinetics and mechanism of reactions

Abstract: The study of the kinetics of the addition of trithiocyanuric acid to oxiranes (i.e., ethylene oxide and propylene oxide) in DMSO solution in the presence of triethylamine as a catalyst is described. The effects of the acid group concentration, the concentration of oxirane, and the catalyst on the course of the reaction was studied. The rate equation describing the addition was derived. The reaction order with respect to the oxirane, catalyst, and reactive groups of the acid were 0.5, 0.5, and 1.5, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This is taken as the average value obtained for three different temperatures. The curves, obtained with the long-time isothermal scanning, were used to determine the degree of conversion and rate of cure using the traditional procedure of the reaction heat evaluation. , Typical plots of conversion (α) versus time of the neat epoxy cured at various temperatures of study are shown in Figure a. The conversion (α) is calculated from the ratio of the heat of cure at time, t , over the total heat generated by the epoxy-anhydride reaction.…”
Section: Resultsmentioning
confidence: 99%
“…This is taken as the average value obtained for three different temperatures. The curves, obtained with the long-time isothermal scanning, were used to determine the degree of conversion and rate of cure using the traditional procedure of the reaction heat evaluation. , Typical plots of conversion (α) versus time of the neat epoxy cured at various temperatures of study are shown in Figure a. The conversion (α) is calculated from the ratio of the heat of cure at time, t , over the total heat generated by the epoxy-anhydride reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In previous articles, the kinetics and mechanism of the addition of TTCA to oxiranes have been described 3. In this article, only the initial stages of the reaction of TTCA with PO and ECH are described.…”
Section: Introductionmentioning
confidence: 98%
“…As previously described, 1, 2 reactions of trithiocyanuric acid (TTCA) with an excess of ethylene oxide or propylene oxide in DMF and in the presence of triethylamine as a catalyst yield polyetherols containing s ‐triazine rings. Their structure can be described by with R = H, CH 3 , and …”
Section: Introductionmentioning
confidence: 99%
“…1 The kinetics and mechanism of the addition of TTCA to ethylene oxide and propylene oxide were also described. 2 This article deals with the addition of the same TTCA to epichlorohydrin (ECH), which is, in practice, an oxirane of a great importance. As an asymmetric compound (like propylene oxide), ECH produces two isometric products: the normal and the abnormal one 3, 4 of the respective moieties: …”
Section: Introductionmentioning
confidence: 99%